MORFOLOGI TASGHIR DALAM BAHASA ARAB DAN KONTRIBUSINYA TERHADAP PEMAHAMAN NUANSA MAKNA DALAM HADIS NABI - Intan Nazmi Nurlaila (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to explore the morphological phenomenon of tasghīr in Arabic and its contribution to understanding the nuanced meanings within the sayings (ḥadīths) of the Prophet Muhammad ﷺ. Tasghīr, often translated as "diminutive," is not merely a morphological marker indicating smallness, but it also conveys rich connotative meanings such as affection, endearment, modesty, or even gentle rebuke. In prophetic communication, the Prophet ﷺ frequently utilized linguistic strategies like tasghīr to soften his speech and emotionally engage his audience. By employing a qualitative method through library research, this paper examines the patterns and functions of tasghīr from the perspective of Arabic morphology (ṣarf) and analyzes selected ḥadīths in which the Prophet ﷺ uses diminutive forms. The findings reveal that tasghīr serves not only grammatical functions but also rhetorical and pedagogical purposes, contributing to a more profound appreciation of the Prophet’s language style. Understanding the use of tasghīr enhances the interpretation of ḥadīths beyond the literal meaning and unveils emotional and spiritual layers embedded in the prophetic discourse. This study underscores the importance of morphological awareness in classical Arabic for a comprehensive grasp of Islamic texts.